The development of EFL examinations in Haiti: Collaboration and language assessment literacy development. (October 2018) - Baker, Beverly A.; Riches, Caroline
Research was conducted during the delivery of a series of workshops on language assessment with Haitian teachers in the spring of 2013. The final products of these workshops were several revised national English examinations presented to the Haitian Ministry of Education and Professional Training (MENFP). The research goal was to examine the language assessment literacy (LAL) development of both teachers and language assessment specialists during this collaboration. Data included the compiled feedback from Haitian teachers on draft examinations during the workshops, as well as survey and interview responses immediately following the workshops. Results reveal the complementary expertise of teachers and specialists, which facilitated LAL development by both parties. Results also identified challenges in collaborative decision making and consensus building to be addressed in future projects.